Diversity in human placental microvascular endothelial cells and macrovascular endothelial cells. (November 2018) - Huang, Xiaojie; Jia, Linyan; Qian, Zhen; Jia, Yuanhui; Chen, Xiao; Xu, Xianghong; Chang, Xinwen; Liu, Ming; Wang, Kai
Highlights: HPMECs were successfully isolated and maintained endothelial phenotypes. HPMECs and HUVECs had different expression of eNOS, PROKR1 and PROKR2. Under the stimulation of EG-VEGF, HPMECs' response is more strongly than HUVECs. Microarray analysis revealed transcriptional changes between HPMECs and HUVECs. Abstract: Angiogenesis is fundamental to normal placental development, and aberrant angiogenesis contributes substantially to placental pathologies. Placental angiogenesis is a pivotal process that plays a key mechanistic role in the elaboration of the placental villous tree, which is mainly taken by human placental microvascular endothelial cells (HPMECs), present in the fetal capillaries of chorionic villi, and macrovascular human umbilical vein endothelial cells (HUVECs) also play a role in this process. These are the two types of endothelial cells that form the placenta and differ in morphology and function. The placental vasculature represents a distinct territory that is highly specialized in structure and function. To distinguish the differences between HPMECs and HUVECs, we isolated HPMECs by paramagnetic particle separation and HUVECs through trypsinization and validated their characteristics. Then, we examined their response to fibroblast growth factor 2 (FGF2), vascular endothelial growth factor (VEGF) and endocrine-gland-derived vascular endothelial growth factor (EG-VEGF), as well as the underlying signaling mechanisms and their transcriptomes. We found that cultured HPMECs and HUVECs took up DiI-Ac-LDL and formed capillary-like tube structures on Matrigel. HPMECs and HUVECs had different expressions of eNOS, PROKR1 and PROKR2, and these characteristics substantiate the endothelial nature of cultured cells. FGF2 and VEGF stimulated the proliferation and migration of HPMECs and HUVECs via activation of PI3K/AKT1 and MEK1/MEK2/ERK1/ERK2. Interestingly, EG-VEGF increased the proliferation and migration of HPMECs via only MEK1/MEK2/ERK1/ERK2 and not PI3K/AKT1. Microarray analysis showed that there were some differentially expressed genes between HPMECs and HUVECs. Gene ontology analysis indicated that the differentially expressed genes were highly related to G-protein coupled receptor signaling pathway, angiogenesis, L-lysine transmembrane transport and blood vessel remodeling. These data provided evidence of heterogeneity between microvascular HPMECs and macrovascular HUVECs that most likely reflected significant differences in endothelial cell function in the two different cellular environments.